The Influence of Knowledge and Leadership on Clinical Risk Management with Patient Safety Culture as an Intervening Variable at PMI Hospital - Wulandari Dyah Ayu; Natsir Nugroho; Idrus Just’at (Jurnal Mahasiswa Ilmu Kesehatan, 2024)
The lack of the leadership function in monitoring and evaluation, the limited training on patient safety is suspected to have resulted in a low safety culture and clinical risk management. This study aims to determine the influence of transformational leadership, patient safety knowledge and culture on clinical risk management at PMI Hospital. Design of a cross-sectional study, 138 nurses in August 2024. Simple random sampling technique, the independent variable is knowledge about patient safety goals and transformational leadership; the dependent variable of clinical risk management, and the intervening variable of patient safety culture. Descriptive analysis shows that PMI Hospital has nurses who have high knowledge of patient safety targets, with a charismatic leadership style, and a communicative patient safety culture. The results show that knowledge of patient safety goals, transformational leadership, and patient safety culture simultaneously and partially have a significanteffect on clinical risk management so that high knowledge, charismatic leadership, and communicative patient safety culture are proven to encourage improvements in clinical risk management at PMI Hospital.